2004
DOI: 10.1007/s00216-004-2815-7
|View full text |Cite
|
Sign up to set email alerts
|

Determination of inorganic arsenic in white fish using microwave-assisted alkaline alcoholic sample dissolution and HPLC-ICP-MS

Abstract: An analytical method for the determination of inorganic arsenic in fish samples using HPLC-ICP-MS has been developed. The fresh homogenised sample was subjected to microwave-assisted dissolution by sodium hydroxide in ethanol, which dissolved the sample and quantitatively oxidised arsenite (As(III)) to arsenate (As(V)). This allowed for the determination of inorganic arsenic as a single species, i.e. As(V), by anion-exchange HPLC-ICP-MS. The completeness of the oxidation was verified by recovery of As(V) which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
17
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 32 publications
4
17
0
2
Order By: Relevance
“…Differences in total As content for benthis-feeding and pelagic-schooling 116 species in the North Sea have been previously observed by Larsen et al [14] They found that plaice (mean…”
supporting
confidence: 63%
“…Differences in total As content for benthis-feeding and pelagic-schooling 116 species in the North Sea have been previously observed by Larsen et al [14] They found that plaice (mean…”
supporting
confidence: 63%
“…Hence, no irreversible protein binding was formed as reported by Larsen et al [26] and Munoz et al [27], despite the high affinity of As III for thiol-groups in proteins [17]. However, since no certified reference materials are available for iAs, the extraction efficiency of iAs from natural incurred samples is difficult to evaluate [28].…”
Section: Extractionmentioning
confidence: 68%
“…However, since no certified reference materials are available for iAs, the extraction efficiency of iAs from natural incurred samples is difficult to evaluate [28]. Several studies have determined the iAs concentration in the CRM TORT-2 (certified for total arsenic), however, no consensus value (concentration range, 0.09-1.1 mg kg −1 ) is reported as recently compiled by Lefroy et al [19,26]. In contrast, the determination of iAs in rice seems not to depend on the extraction approach applied as recently demonstrated in a large interlaboratory study on iAs determination in rice, where consistent results were obtained among different approaches, including the procedure described in the present study [29].…”
Section: Extractionmentioning
confidence: 97%
See 1 more Smart Citation
“…For the determination of inorganic arsenic a method recently applied for the analysis of fish samples was used (Larsen et al. 2005).…”
mentioning
confidence: 99%